Objective and Subjective Video Quality Assessment in Mobile Devices for Low-Complexity H.264/AVC Codecs - Melo, Mateus; Goebel, Jones; Farias, Daniel; Santos, Cristiano; Tavares, Tatiana; Corrêa, Guilherme; Zatt, Bruno; Porto, Marcelo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
This paper discusses results from a quality evaluation experiment involving videos on mobile devices encoded with different configurations of H.264/AVC. The impact of not employing the Fractional Motion Estimation (FME) and the Deblocking Filter (DBF) during the encoding process was also analyzed in the experiments presented in this paper. In order to perform the quality assessment, the objective metrics Structural Similarity (SSIM) and Peak Signal-to-Noise Ratio (PSNR) were used. The subjective evaluation was conducted in two different mobile devices by employing the Mean Opinion Score (MOS) with single stimulus. The obtained results have shown different levels of quality degradation for both modifications. In addition, they led to the conclusion that larger screen devices present a more accentuated drop in subjective quality than small screen devices.